2022
DOI: 10.3390/cancers14215289
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Role of Anti-PD-L1 and Anti-CTLA-4 mAbs on Different Lymphocytes Subpopulations in TNBC

Abstract: Antibody-based cancer immunotherapy includes monoclonals against immune checkpoints (ICs), to modulate specific T cell responses against cancer. NK cells are a newly emerging target for immune checkpoint receptor inhibition in cancer immunotherapy, as ICs are also expressed on NK cells in various cancers. The latter cells are becoming attractive targets for cancer immunotherapy, as they are effector cells similar to CTLs, exerting natural cytotoxicity against primary tumor cells and metastasis, and they are ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…While immunotherapy does not have a robust response in general to breast cancer patients, it has been shown that a subset of TNBCs has high TMB and high TILs, like those observed in melanoma or lung cancer, which may be treated with immune checkpoint inhibitors. Consequently, developing immunotherapies that target TNBC has become possible due to its immunogenic nature [ 111 ]. Recently, the FDA approved atezolizumab combined with nab-paclitaxel for treating metastatic and unresectable programmed cell death ligand 1 (PD-L1)-positive TNBC [ 112 ].…”
Section: Treatment Strategies For Tnbcmentioning
confidence: 99%
“…While immunotherapy does not have a robust response in general to breast cancer patients, it has been shown that a subset of TNBCs has high TMB and high TILs, like those observed in melanoma or lung cancer, which may be treated with immune checkpoint inhibitors. Consequently, developing immunotherapies that target TNBC has become possible due to its immunogenic nature [ 111 ]. Recently, the FDA approved atezolizumab combined with nab-paclitaxel for treating metastatic and unresectable programmed cell death ligand 1 (PD-L1)-positive TNBC [ 112 ].…”
Section: Treatment Strategies For Tnbcmentioning
confidence: 99%
“…Human peripheral blood mononuclear cells (PBMCs) were isolated from the blood of healthy donors using a Greiner Leucosep ® tube (Sigma-Aldrich, St. Louis, MO, USA) following the manufacturer's instructions, as previously reported [16,19,[23][24][25], and frozen in 90% FBS plus 10% dimethyl sulfoxide (DMSO) solution until use. Cryopreserved cell vials were gently thawed using RPMI 1640 medium supplemented with 1% L-glutamine, 1% CTLWash™ (Immunospot by Cellular Technology Limited, Shaker Heights, Cleveland, OH, USA) and 100 U/mL Benzonase (Merck Millipore, Darmdstadt, Germany) and washed via centrifugation.…”
Section: The Isolation Of Human Peripheral Blood Mononuclear Cellsmentioning
confidence: 99%
“…As negative controls, the co-cultured cells were analyzed in the absence of treatments or in the presence of a human-unrelated IgG used at the same concentration. The cell supernatants were collected at the end of incubation, and the level of lactate dehydrogenase (LDH) released by the cells was evaluated as a marker of tumor cell lysis and expressed as a percentage with respect to the max lysis obtained after treatment with 10% Triton X-100, following the manufacturer's recommendations for the LDH detection kit (Thermofisher Scientific, Rockford, IL, USA) [18,19].…”
Section: Cytotoxicity Assays and Ldh Detectionmentioning
confidence: 99%
See 2 more Smart Citations